A New In Silico Comparison of the Relative Affinity of Enantiomeric Chloroquine (CQ) and Hydroxychloroquine (HCQ) for ACE2 - Carlos Naranjo-Castañeda; Marco A. García-Revilla; Eusebio Juaristi (Pharmaceuticals)
Background/Objectives: Chloroquine (CQ) and hydroxychloroquine (HCQ) have been the subject of debate in the treatment of COVID-19 due to the lack of conclusive evidence regarding their efficacy and safety. Our study aims to investigate the molecular interaction between the enantiomers of CQ and HCQ with angiotensin-converting enzyme 2 (ACE2), focusing on the binding mechanism, affinity, and selectivity. Methods: We used in silico methods, including molecular docking, molecular dynamics, and binding free energy calculations using the MM-PBSA method, to evaluate the interaction between the enantiomers of CQ and HCQ with ACE2. Results: We identified three main interaction sites on ACE2 (α, β, and γ) with distinct characteristics based on the pocket size, hydrophilic/hydrophobic characteristics, and affinity energy. We observed that protonation states and ionic strength significantly influence the binding affinity and specificity. In particular, the selectivity of the β-site, characterized by its smaller size and hydrophilic residues, is preferential for species with the (R) configuration, whereas the α and γ binding sites, with a larger size and amphiphilic residues, have greater affinity for the (S) enantiomer of CQ and HCQ. Furthermore, ionic strength can affect ligand binding by modulating electrostatic interactions, molecular conformation, solvation, and the stability of the complex. Conclusions: Our findings reveal that protonation states and the ionic strength substantially impact the binding affinity and specificity, regulated by spatial and polar–electrostatic complementarity, as well as hydrophobic contributions. These results suggest that understanding the interaction between CQ and HCQ enantiomers with ACE2 could be useful for the design of novel therapies against COVID-19.